THE STUDY OF THE STRUCTURE OF ATOMS OF ELEMENTS OF LARGE AND SMALL PERIODS BY A MODERN METHOD - Raxmonov Sh.T.; Ikhtiyarova G.A. (Research Focus International Scientific Journal, 2023)
This article describes the ways of explaining the topic “Atomic structure of small and large period elements” in a new interpretation. Of course, this recommendation is important for teachers of chemistry, which describes ways of explaining the topic in a broad manner based on a new and innovative approach. Because nowadays innovations are used in every field, including education. It is important that the teacher aims to improve the quality of education by using modern pedagogical technologies and innovative methods in each subject. This guide is definitely important for chemistry teachers.